Manju Kapur’s Shagun: Conflict between Individual Freedom and Patriarchy - Dr. Mangesh Madhukar Gore, (The Creative Launcher, 2017)
Manju Kapur’s novel, Custody (2011) reveals some of the significant aspects of human relation such as the conflict between husband and wife and its dimensions. In recent time, the notion of human relationship is under the process of change due to various striking and contradictory factors that lead them to separation. The issue of an independent identity leads husband and wife in conflicting situation. The narrative leads with the tension of human relation against the issues like education, modernity and humanity. A feeling of discontent, shock and fear, misunderstanding, lack of dedication, unfaithful nature, miscommunication and constant quest of identity are portrayed in Custody. It is through the character of Shagun Manju Kapur deals with conflict between individual freedom aspired by the modern women and patriarchy that imposes limitations on personal space in the family.